Protective Effects of Sodium (±)-5-Bromo-2-(α-Hydroxypentyl) Benzoate in a Rodent Model of Global Cerebral Ischemia - Gao, Yuan; Li, Miao; Wang, Yan; Li, Zhengqi; Fan, Chenyu; Wang, Zheng; Cao, Xinyu; Chang, Junbiao; Qiao, Hailing (Frontiers in Pharmacology, 2017)
The aim of the current study was to explore the protective effects of sodium (±)-5-bromo-2-(α-hydroxypentyl) benzoate (brand name: brozopine, BZP) in a rat model of global cerebral ischemia. The rat model was established using a modified Winocur’s method; close postoperative observation was conducted at all times. Neurological function was detected through prehensile traction and beam-walking test. BZP reduced mortality and prolonged the survival time of rats with global cerebral ischemia, within 24 h. There was a decreased survival rate (60%) in the Model group, while the survival rate of the BZP (3 and 12 mg/kg) remarkably increased the survival rate (to 80% and 90%, respectively), in a dose-dependent manner. Compared with the Model group (survival time: 18.50 h), the administration of BZP (0.75, 3, and 12 mg/kg) prolonged the survival time (to 20.38 h, 21.85 h, and 23.90 h, respectively), particularly in BZP 12 mg/kg group (P < 0.05). Additionally, the BZP (12 mg/kg) group exhibited an improvement in their motor function (P < 0.05). The BZP groups (0.75, 3, and 12 mg/kg) displayed significantly reduced necrosis and the percentage of apoptotic cells (P < 0.05 and P < 0.01, respectively). Compared with Model group, BZP (0.75, 3, and 12 mg/kg) increased the NeuN optical density values (P < 0.01). Rats with global ischemia had a high expression of Cyt-c, Caspase-3 and the Bax/Bcl-2 ratio compared with sham group (P < 0.01). BZP (0.75, 3, and 12 mg/kg), however, reduced the expression of Cyt-c, Caspase-3, and the Bax/Bcl-2 ratio, in a dose-dependent manner (P < 0.01). There was low expression of p-Akt and PI3K in Model group, compared with the sham group (P < 0.01). Meanwhile, BZP (0.75, 3, and 12 mg/kg) increased the expression of p-Akt and PI3K in a dose-dependent manner (P < 0.01). We also found the expression of Cyt-c, Caspase-3, Bax/Bcl-2 ratio, PI3K, p-Akt and comprehensive score were directly related. In conclusion, BZP had therapeutic potential and prevented stroke in rat model of global cerebral ischemia. The underlying mechanisms may be related to the inhibition of apoptosis and activation of the survival -signaling -pathway.